A novel, DSP based algorithm for optimizing the harmonics and reactive power under non-sinusoidal supply voltage conditions - George, S.; Agarwal, V. (IEEE transactions on power delivery, 2005)
This paper presents a simple control algorithm for a shunt active filter for compensation of harmonics and reactive power under nonsinusoidal supply voltage conditions. Under nonsinusoidal supply conditions, any attempt to achieve unity power factor results in a nonsinusoidal current, which increases the total harmonic distortion (THD). On the other hand, attempt at getting harmonic free current may not yield unity power factor because of the harmonics present in the voltage waveform. The proposed algorithm optimizes this trade-off using the Lagrange multiplier technique and achieves the best compromise. It does not employ the normally used p-q theory and is applicable to both single phase and three phase systems. With the proposed technique, it is possible to obtain an optimized power factor satisfying the specified THD limit. The algorithm has been tested under various supply and load conditions using MATLAB simulations and validated with an experimental prototype based on DSP TMS320LF2407A.